OPTIMALISASI PELAYANAN PUBLIK MELALUI ELECTRONIC TRAFFIC LAW ENFORCEMENT (E-TLE) OLEH DITLANTAS POLDA JAWA TENGAH DI WILAYAH KOTA SEMARANG - Nur Tamia, Diva; Subowo, Ari; Santoso, R. Slamet (Journal of Public Policy and Management Review, 2024)
Effective and efficient traffic law enforcement is the main focus in improving public services in urban areas. One of the efforts taken is the implementation of Electronic Traffic Law Enforcement (E-TLE) by the Central Java Regional Police Traffic Directorate (Ditlantas Polda) in Semarang City. This study aims to analyze the optimization of public services through the implementation of E-TLE in traffic law enforcement in the region and identify success factors in this optimization. Study findings show that the implementation of E-TLE has increased the efficiency of law enforcement, accelerated action against violations, and reduced traffic accidents. Apart from that, public services also benefit from this system because the law enforcement process is faster and more transparent, increasing public trust in the police. The results of this research contribute to the understanding of the importance of technology in improving public services and the effectiveness of traffic law enforcement in metropolitan cities. Next steps could include expanding the E-TLE network and increasing public awareness of the importance of complying with traffic rules to create a safer and more orderly environment for all road users.